Intersection of Stress and Gender in Association With Transitions in Past Year DSM-5 Substance Use Disorder Diagnoses in the United States. (January 2018) - Verplaetse, Terril L.; Moore, Kelly E.; Pittman, Brian P.; Roberts, Walter; Oberleitner, Lindsay M.; Smith, Philip H.; Cosgrove, Kelly P.; McKee, Sherry A.
Background: Stress contributes to the development and maintenance of substance use disorders, with some research suggesting that the impact of stress on substance use disorders is greater in women. However, this has yet to be evaluated in a national dataset, across major substances of abuse. Methods: Using data from the newly available U.S. National Epidemiologic Survey on Alcohol and Related Conditions (NESARC; Wave 3; n  = 36, 309), we evaluated relationships among past year stressful life events (0 or 1 vs. 2+ events, range 0–16) and gender, and their association with transitions (new vs. absent cases; ongoing vs. remitted cases) in Diagnostic and Statistical Manual of Mental Disorders Fifth Edition alcohol use disorder, tobacco use disorder, cannabis use disorder, and nonmedical prescription opioid use disorder diagnoses. Results: Having two or more stressful life events in the past year increased the odds of having a new alcohol use disorder, tobacco use disorder, cannabis use disorder, and opioid use disorder (OR = 3.14, 2.15, 5.52, and 3.06, respectively) or ongoing alcohol use disorder, tobacco use disorder, and cannabis use disorder (OR = 2.39, 2.62, and 2.95, respectively) compared to zero or one stressful life event. A stress by gender interaction for new vs. absent alcohol use disorder demonstrated that having two or more stressful life events was associated with increased odds of new alcohol use disorder in men (OR = 2.51) and even greater odds of new alcohol use disorder in women (OR = 3.94). Conclusions: Results highlight that stress is a robust factor in both men and women with new or ongoing substance use disorders, and that effective treatments for substance use should consider the role of stress in addiction etiology and maintenance. There was little evidence for gender differences in the role of stress on transitions in substance use disorders, except for the onset of alcohol use disorders. Given that rates of alcohol use disorders are increasing in women, the impact of stress needs to be considered.